Central nervous system tuberculoma with miliary tuberculosis in the elderly. (2020) - Tetsuka, Syuichi; Suzuki, Tomohiro; Ogawa, Tomoko; Hashimoto, Ritsuo; Kato, Hiroyuki
Highlights: Elderly CNS tuberculoma may not have systemic signs of infection such as a fever. Tuberculosis (TB) in older persons can result in delay in diagnosis and initiation. Case is disseminated TB- military TB as well as CNS tuberculomas in the elderly. MRI showed multiple well‑defined enhancing lesions in the brain. In the elderly, early diagnosis for TB is critical. Abstract: The aging phenomenon of tuberculosis (TB) patients is recognized all over the world, but no country is as prominent as Japan. Central nervous system (CNS) TB includes clinical entities: tuberculous meningitis, intracranial tuberculoma, and clinical features of CNS TB in the elderly may be atypical, non-specific, and confused with concomitant age-related diseases. Atypical clinical manifestations of TB in older persons can result in delay in diagnosis and initiation of treatment. A 91-year-old woman was brought to our emergency department after her family noted her altered mental status. Chest computed tomography confirmed miliary opacities. The cerebrospinal fluid (CSF) analysis showed elevated protein level, low glucose level, and a lymphocytic pleocytosis. Brain magnetic resonance imaging (MRI) showed multiple well‑defined enhancing lesions in the cerebral and cerebellar hemispheres and the pons, suggestive of tuberculomas. Smear, culture, and polymerase chain reaction (PCR) tests confirmed Mycobacterium tuberculosis in the sputum and aspirate. Based on the CSF and brain MRI findings and the sputum microbiology results indicating the presence of M. tuberculosis in the sputum and gastric aspirate, the patient was diagnosed with CNS tuberculoma. The onset of TB is mainly associated with decreased immunity; however, several other factors such as comorbidities, decreased activity, dysphagia, and malnutrition, which influence one another, also influence the development of TB in the elderly. Because the mortality rate of TB increases rapidly with age, reaching approximately 30 % among the elderly, early diagnosis is critical.